1994
DOI: 10.1152/ajpregu.1994.266.3.r863
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of respiration and heart rate during wakefulness and sleep in elephant seal pups

Abstract: Although breath holding during diving has been studied extensively in seals, the recent observation that these mammals also exhibit long-duration apnea while apparently sleeping has not been systematically examined. This project examined sleep apnea in northern elephant seal pups (Mirounga angustirostris). The animals exhibited a sequential sleep pattern of wakefulness-slow-wave sleep (SWS)-rapid eye movement (REM) sleep that resembled the normal pattern of mammalian sleep. The typical respiratory pattern duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 7 publications
9
63
0
Order By: Relevance
“…Although this could be true, an important interesting fact is that the majority of both [44][45][46][47][48] . Some pinnipeds, such as Caspian seals (Phoca caspica) [49] , harp seals (Pagophilus groenlandica) [50] and elephant seals (Mirounga angustirostris) [51] , do not exhibit inter-hemispheric asymmetry in slow-wave generation during NREM sleep, suggesting that unihemispheric sleep is typical of fur seals and sea lions but not of all semi-aquatic pinnipeds.…”
Section: Continuedmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this could be true, an important interesting fact is that the majority of both [44][45][46][47][48] . Some pinnipeds, such as Caspian seals (Phoca caspica) [49] , harp seals (Pagophilus groenlandica) [50] and elephant seals (Mirounga angustirostris) [51] , do not exhibit inter-hemispheric asymmetry in slow-wave generation during NREM sleep, suggesting that unihemispheric sleep is typical of fur seals and sea lions but not of all semi-aquatic pinnipeds.…”
Section: Continuedmentioning
confidence: 99%
“…When harp seals sleep on land, they exhibit ~3.2% REM sleep, but in water they barely go into REM (0.5%) [50] . Castellini et al compared sleep in northern elephant seal pups under dry and wet conditions and demonstrated that the length of REM sleep episodes significantly decreases under wet conditions [51] . Similar characteristics have also been recorded in northern fur seals [55] .…”
Section: Ridgway Et Al In 1975 For the First Time Studied Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purposes of this paper, rest-associated apneas were characterized by breath-holds with eyes closed, occasional facial twitching and lack of body movements (Castellini et al, 1994;Ponganis et al, 2006;Stockard et al, 2007). Following the restassociated apnea trials, animals were then transferred to a shallow water tank and allowed to submerge freely for another 6h.…”
Section: Rest-and Voluntary-submersion-associated Apneasmentioning
confidence: 99%
“…Apnea in seals is characterized by a series cardiovascular adjustments (reduction in cardiac output, bradycardia, peripheral vasoconstriction) that allow seals to maximize the use of their oxygen stores but at the same time result in blood oxygen depletion and blood flow redistribution towards obligatory oxygendependent tissues, exposing seals to critical levels of ischemia and hypoxemia (Castellini et al, 1994;Elsner, 1999;Kooyman and Ponganis, 1998;Stockard et al, 2007). At the end of an apnea bout, an increase in cardiac output and ventilation restores blood flow to tissues and blood oxygen content, presenting seals with potential increases in oxidant production and oxidative stress (Elsner et al, 1998;Zenteno-Savín et al, 2002).…”
Section: Introductionmentioning
confidence: 99%